ANALYSIS OF FIXED ASSET DEVELOPMENT IN PEMATANGSIANTAR CITY - Aqila, Syauqi; Ramadhani Daulay, Kesya Aulia; Muda, Iskandar (Journal Economics Technology And Entrepreneur, 2025)
This study aims to analyze the management and condition of fixed assets in Pematangsiantar City, particularly in terms of acquisition, depreciation, and the causes of increases and decreases in the value of fixed assets during the 2023-2024 period. Fixed assets are important assets that have a useful life of more than 12 (twelve) months for use in government or utilized by the general public. The method used in this study is a descriptive study with a quantitative approach, using secondary data obtained from regional financial reports available on the official website of the Pematangsiantar City Regional Financial Management Agency. The results of the analysis show that the management of fixed assets in Pematangsiantar City still faces several obstacles, such as suboptimal recording, unscheduled maintenance, and the lack of an effective monitoring system. Therefore, it is necessary to improve the administration and supervision system of fixed assets so that regional assets can be utilized optimally and sustainably. This study is expected to provide a deeper understanding of the accounting treatment of fixed assets and become a reference for the government in improving fixed asset management to support better regional development.